2016
DOI: 10.15698/mic2016.07.512
|View full text |Cite
|
Sign up to set email alerts
|

Filamentation protects Candida albicans from amphotericin B-induced programmed cell death via a mechanism involving the yeast metacaspase, MCA1

Abstract: The budding yeast Candida albicans is one of the most significant fungal pathogens worldwide. It proliferates in two distinct cell types: blastopores and filaments. Only cells that are able to transform from one cell type into the other are virulent in mouse disease models. Programmed cell death is a controlled form of cell suicide that occurs when C. albicans cells are exposed to fungicidal drugs like amphotericin B and caspofungin, and to other stressful conditions. We now provide evidence that suggests that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 52 publications
(78 reference statements)
1
20
0
1
Order By: Relevance
“…Filamentation in the bcy1/bcy1 mutant could be a strategy of cells to avoid cell death or to improve their anti-stress abilities. Consistent with our study, Laprade et al (2016) recently reported that filamentation of C. albicans provides protection against antifungal-induced programmed cell death (Laprade et al, 2016). …”
Section: Discussionsupporting
confidence: 92%
“…Filamentation in the bcy1/bcy1 mutant could be a strategy of cells to avoid cell death or to improve their anti-stress abilities. Consistent with our study, Laprade et al (2016) recently reported that filamentation of C. albicans provides protection against antifungal-induced programmed cell death (Laprade et al, 2016). …”
Section: Discussionsupporting
confidence: 92%
“…Rocaglate-induced cell death displays phenotypic hallmarks of apoptosis. Phenotypes associated with metazoan apoptosis have been observed in pathogenic fungi under conditions of exposure to various environmental stresses (22)(23)(24). To investigate whether these phenotypes occur in rocaglate-treated C. auris, we first monitored loss…”
Section: Figmentioning
confidence: 99%
“…Finally, although the topic of apoptosis in a single-celled organism remains controversial, multiple reports have described apoptosis-like responses in fungal species. For example, deletion of cell cycle genes such as CDC48 (20), expression of mammalian proapoptotic markers such as Bax (21), or treatment with H 2 O 2 (22) or amphotericin B (23,24) was shown to lead to phenotypes characteristic of apoptotic cell death. These include membrane disruption and phosphatidylserine exposure, nucleosomal DNA fragmentation, calcium influx, increased levels of reactive oxygen species (ROS), and mitochondrial depolarization (15,16).…”
mentioning
confidence: 99%
“…How could a single amino acid change in this insert region affect filamentation or other processes that require the efficient functioning of the Flo8 as a transcriptional activator? If filamentation benefits the AmB‐insulted fungus by helping it to protect itself from the action of AmB, as appears to be the case for C. albicans , and if the passage‐mediated increase in filamentation or filamentation competence is also an adaptive or beneficial step for the fungus, then a Flo8 S → N mutation found precisely in an AmB‐resistant strain would suggest an increase, rather than a decrease, in filamentation or filamentation competence, and thus possibly an increase in the net efficiency of transcription events that promote such properties.…”
mentioning
confidence: 99%
“…11 Correspondingly, in the congeneric species Candida albicans, experimental results strongly suggest that filamentation protects the yeast cells against programmed cell death induced by the antifungal drug amphotericin B (AmB). 12,13 Other processes in which Flo8 and its target genes are (or might reasonably be considered to be) involved, and that are also relevant for understanding C. auris, include an aggregation that has been noted for this species, formation of biofilms in clinical settings, adhesion processes within the host, and adhesion to dry objects or survival under other adverse conditions that may partly account for its unusual resilience and transmission in or between hospitals (see 10 and references therein).…”
mentioning
confidence: 99%